Catalase Activity as a Bio-Indicator of Lead+Nickel Toxicity in Carnivorous Fish, Channa striata: Response of CAT activity in fish - Arshad, Rabia; Abdullah, Sajid; Naz, Huma; Abbas, Khalid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
The freshwater ecosystems are extensively polluted with heavy metals discharged from industrial, domestic, and other human activities. These metals are significant stimulators of oxidative stress in aquatic organisms, especially fish, leading to the creation of reactive oxygen species. Therefore, current research was conducted to elucidate the toxic effect of heavy metals mixture (Pb+Ni) on catalase activity in various organs (gills, liver, kidney, brain, muscle and heart) of carnivorous fish, Channa striata exposed to sub-lethal concentrations (1/3rd, 1/4th and 1/5th of LC50) for a period of 14-day. Fish were sampled for enzyme study after 7 and 14-days. Results showed that all concentrations of metals mixture significantly decreased the CAT activity in selected organs of the fish however, maximum depletion was observed in 1/3rd of LC50 concentration followed by the order of 1/4th>1/5th. The CAT activity was decreased with increasing the concentration and duration of exposure.